2018
DOI: 10.1101/383992
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chromosome-scale assemblies reveal the structural evolution of African cichlid genomes

Abstract: Background

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 105 publications
(176 reference statements)
2
67
0
Order By: Relevance
“…The genomic population structure and linkage disequilibrium (LD) have also been reported using dense SNP panels in different tilapia populations (Xia et al, 2014;Joshi et al, 2018;Conte et al, 2019;Yoshida et al, 2019c). For farmed Nile tilapia, strong admixture among three different farmed populations from Latin America and a rapid decrease in LD with increasing inter-marker distance were observed (Yoshida et al, 2019c), in accordance with Xia et al (2014), who found similar LD patterns for GIFT populations from South Africa, Singapore and China.…”
Section: Population Genetic Studiessupporting
confidence: 56%
“…The genomic population structure and linkage disequilibrium (LD) have also been reported using dense SNP panels in different tilapia populations (Xia et al, 2014;Joshi et al, 2018;Conte et al, 2019;Yoshida et al, 2019c). For farmed Nile tilapia, strong admixture among three different farmed populations from Latin America and a rapid decrease in LD with increasing inter-marker distance were observed (Yoshida et al, 2019c), in accordance with Xia et al (2014), who found similar LD patterns for GIFT populations from South Africa, Singapore and China.…”
Section: Population Genetic Studiessupporting
confidence: 56%
“…PacBio sequencing was carried out on the PacBio RS II platform with P6-C4 chemistry using 9 SMRT cells and on the PacBio Sequel platform using 9 additional SMRT cells. Illumina and PacBio sequencing reads were aligned to the reference assembly of a M. zebra 'Mazinzi Reef' NoB male individual sequenced with PacBio [41], (publicly available on NCBI, Accession: GCA_000238955.4, [42]) with BWA [43] and NGM-LR [44], respectively. BWA alignments were then run through Picard version 2.1.0 'MarkDuplicates' to identify PCR duplicates.…”
Section: Methodsmentioning
confidence: 99%
“…Morgans (Conte et al, 2018). Thus the 11,000 to 21,000 markers are required for Nile 346 tilapia populations.…”
Section: Philippines 300mentioning
confidence: 99%